2007
DOI: 10.1007/s00428-007-0384-9
|View full text |Cite
|
Sign up to set email alerts
|

Frequency and diagnostic patterns of lymphomas in liver biopsies with respect to the WHO classification

Abstract: The recent World Health Organization (WHO) classification of hematopoietic and lymphoid tissue tumors represents the first worldwide consensus classification of these malignancies. However, the applicability of this classification to a representative number of hepatic lymphomas in liver biopsy specimens has not yet been investigated. The frequency and infiltration pattern of a series of 205 liver biopsies with lymphoma manifestations was analyzed with the aid of immunohistochemical and molecular pathological a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
33
0
2

Year Published

2008
2008
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(37 citation statements)
references
References 26 publications
(28 reference statements)
2
33
0
2
Order By: Relevance
“…28,29 Interestingly, marginal-zone B-cell lymphoma, the most important differential diagnosis of hepatic pseudolymphoma, showed this pattern in only one case (6% of 16 cases). 28,29 It is still ambiguous whether or not a characteristic pattern of infiltration at the edge of hepatic pseudolymphoma can be observed in low-grade B-cell lymphoma. But, unique features observed in needle biopsies (Figure 4) was not described in those two studies.…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…28,29 Interestingly, marginal-zone B-cell lymphoma, the most important differential diagnosis of hepatic pseudolymphoma, showed this pattern in only one case (6% of 16 cases). 28,29 It is still ambiguous whether or not a characteristic pattern of infiltration at the edge of hepatic pseudolymphoma can be observed in low-grade B-cell lymphoma. But, unique features observed in needle biopsies (Figure 4) was not described in those two studies.…”
Section: Discussionmentioning
confidence: 98%
“…Two previous studies examined patterns of hepatic infiltration in malignant lymphoma. 28,29 The studies examined 294 cases in total, including 76 cases of low-grade B-cell lymphomas (marginal-zone B-cell lymphoma, B-CLL, mantle cell lymphoma, and follicular lymphoma). 28,29 The patterns of hepatic infiltration were classified into nodular, portal, and sinusoidal.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Two recent studies have identified three main patterns of hepatic involvement in lymphoproliferative disease – portal, nodular and sinusoidal (Figure ). In many cases, more than one of these three basic patterns is present.…”
Section: Angiosarcomamentioning
confidence: 99%
“…Morphologic and immunophenotypic examinations of the sample yielded the diagnosis of extranodal marginal zone lymphoma, a subtype of B-cell peripheral neoplasms [4]. On the basis of the results of the staging workup, we concluded that the nodule was a low-grade B-cell primary hepatic lymphoma.…”
mentioning
confidence: 92%